The effect of spirituality assistance on improving life quality in cancer children - Pratiwi, Etik; Adi, Giri Susilo (International Journal Of Community Medicine And Public Health, 2019)
Background: Cancer is a disease with a high mortality rate.1 States that the death rate from cancer can reach 45% in 2007. Emotional and spiritual dysfunction in children and adolescents can lead to symptoms of depression and is one of the risk factors for suicide.6 Methods: This research is a type of mixed research (mix method), with a sequential explanatory strategy. This strategy is a method of approach by conducting quantitative data collection as the main method then followed by qualitative data collection. Results: There were 30 children who were used as respondents in this study, the majority of whom were male and aged over 13 years. The majority of children experience leukemia. The results of data analysis showed the influence of spirituality assistance on quality of life. The value of the total quality of life of the total respondents conducted by spirituality assistance increased in value by 8,962, from an average value of 75,055 to 84,017. The p value for total quality of life is 0,000. Conclusions: There is an influence of spirituality accompaniment on the quality of life for children with cancer. Children can be invited to worship together with parents, this is an effective coping to motivate them to survive in carrying out their lives and activities everyday even in conditions of illness.